2004
DOI: 10.1097/01.brs.0000132514.33078.da
|View full text |Cite
|
Sign up to set email alerts
|

Soft Tissue Neck Symptoms Following High-Energy Road Traffic Accidents

Abstract: Our study demonstrates a surprisingly low incidence of neck symptoms following high-energy road traffic accidents in which patients sustained unrelated injuries requiring treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
3
0
3
Order By: Relevance
“…Overall, although we had a low incidence of whiplash injury (13%), it was higher than similar studies conducted previously. 68,69 This may well be attributed to thorough inclusion and exclusion criteria applied in selection of the patients and long mean follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…Overall, although we had a low incidence of whiplash injury (13%), it was higher than similar studies conducted previously. 68,69 This may well be attributed to thorough inclusion and exclusion criteria applied in selection of the patients and long mean follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…Income level showed a significant association with treatment cost, but not with duration of treatment ( Table 4 ). Regression analysis results also confirmed that the severity of pain at the time of the CI settlement had a significant influence on cost and duration of treatment after CI settlement (Tables 5 and 6 ) [ 23 ].…”
Section: Resultsmentioning
confidence: 72%
“…По мнению Malik, Lovell [79], хлыстовой травмой считается повреждение мягких тканей шейного отдела позвоночника, полученное пассажиром или водителем автомобиля во время столкновения, при котором возникло резкое ускорение или торможение. Ранее понятие хлыстовой травмы ограничивали гиперэкстензионными повреждениями, возникающими из-за удара в заднюю часть автомобиля.…”
unclassified
“…В ряде исследований удалось выявить взаимосвязь между ускорением, силой удара, с которой произошло столкновение, и вероятностью возникновения хлыстовой травмы и ее исходом. Превалирование хлыстовой травмы после автомобильных происшествий, невозможность предсказать развитие хронических симптомов и отсутствие достоверных клинических и рентгенологических данных наводят на мысль о том, что важным фактором, влияющим на развитие хронических болей в шейном отделе позвоночника после хлыстовой травмы, является физиологическая особенность пациента [79]. Авторами проведено ретроспективное исследование со слепым контролем частоты возникновения симптомов со стороны мягких тканей шейного отдела позвоночника у 36 пострадавших в ДТП с тяжелыми скелетными травмами, но интактным шейным отделом позвоночника.…”
unclassified
See 1 more Smart Citation